Elevated expression of the adhesion GPCR ADGRL4/ELTD1 promotes endothelial sprouting angiogenesis without activating canonical GPCR signalling - Favara, David M. (Sci Rep, 2021)
ADGRL4/ELTD1 is an orphan adhesion GPCR (aGPCR) expressed in endothelial cells that regulates tumour angiogenesis. The majority of aGPCRs are orphan receptors. The Stachel Hypothesis proposes a mechanism for aGPCR activation, in which aGPCRs contain a tethered agonist (termed Stachel) C-terminal to the GPCR-proteolytic site (GPS) cleavage point which, when exposed, initiates canonical GPCR signalling. This has been shown in a growing number of aGPCRs. We tested this hypothesis on ADGRL4/ELTD1 by designing full length (FL) and C-terminal fragment (CTF) ADGRL4/ELTD1 constructs, and a range of potential Stachel peptides. Constructs were transfected into HEK293T cells and HTRF FRET, luciferase-reporter and Alphascreen GPCR signalling assays were performed. A stable ADGRL4/ELTD1 overexpressing HUVEC line was additionally generated and angiogenesis assays, signalling assays and transcriptional profiling were performed. ADGRL4/ELTD1 has the lowest GC content in the aGPCR family and codon optimisation significantly increased its expression. FL and CTF ADGRL4/ELTD1 constructs, as well as Stachel peptides, did not activate canonical GPCR signalling. Furthermore, stable overexpression of ADGRL4/ELTD1 in HUVECs induced sprouting angiogenesis, lowered in vitro anastomoses, and decreased proliferation, without activating canonical GPCR signalling or MAPK/ERK, PI3K/AKT, JNK, JAK/HIF-1α, beta catenin or STAT3 pathways. Overexpression upregulated ANTXR1, SLC39A6, HBB, CHRNA, ELMOD1, JAG1 and downregulated DLL4, KIT, CCL15, CYP26B1. ADGRL4/ELTD1 specifically regulates the endothelial tip-cell phenotype through yet undefined signalling pathways.